2003
DOI: 10.1037/0096-1523.29.2.441
|View full text |Cite
|
Sign up to set email alerts
|

Utterance format effects phonological priming in the picture-word task: Implications for models of phonological encoding in speech production.

Abstract: Picture-word experiments investigating the production of multiword utterances with distractors that are phonologically related to words in noninitial position have yielded inconsistent results, ranging from facilitation to inhibition. A comparison of these studies is complicated by differences in detail. In parallel to the empirical inconsistencies, different theoretical accounts of phonological encoding in speech production have been provided. In the present article, the authors propose a unitary account, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
75
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 33 publications
17
75
2
Order By: Relevance
“…Assuming that the phonological facilitation effect reflects processes at the level of phonological encoding, the phonological properties of the verb, part of the second phonological word and phrase were active before articulation. This result is compatible with results from Costa and Caramazza (2002) and Jescheniak et al (2003), where phonological facilitation was observed for the second phonological word for noun phrases like the red car. This result is also compatible with evidence from noun phrase production, where phonological planning extended two phonological words (Alario & Caramazza, 2002;Miozzo & Caramazza, 1999;Roelofs, 1998).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Assuming that the phonological facilitation effect reflects processes at the level of phonological encoding, the phonological properties of the verb, part of the second phonological word and phrase were active before articulation. This result is compatible with results from Costa and Caramazza (2002) and Jescheniak et al (2003), where phonological facilitation was observed for the second phonological word for noun phrases like the red car. This result is also compatible with evidence from noun phrase production, where phonological planning extended two phonological words (Alario & Caramazza, 2002;Miozzo & Caramazza, 1999;Roelofs, 1998).…”
Section: Resultssupporting
confidence: 82%
“…The words are part of the first and second phonological words. Using the same paradigm, Jescheniak et al (2003) found phonological activation of the object name in noun phrase production in German when it was part of the second and third phonological word (although the effect varied between phonological facilitation and interference). Using a simple picture-naming paradigm, phonological properties outside the first phonological word was seen to affect onset of articulation in noun phrase production in French and Italian (Alario & Caramazza, 2002;Miozzo & Caramazza, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, phonological effects were obtained in the article þ noun production task. Similar results have been reported by Costa and Caramazza (2002), Jescheniak, Schriefers, and Hantsch (2003), Meyer (1996), and Miozzo and Caramazza (1999), although in those studies whole words were used as distractors.…”
Section: Discussionsupporting
confidence: 76%
“…Their argument for this strict threshold is that interlocutors are highly trained to recognize gaps, when they can start their turn. But even if one assumes higher thresholds reaching up to 600 ms (Jescheniak et al, 2003;Schnur et al, 2006) Heldner and argue that the proportion of responses which can be explained by reaction would be lower, but would not be eliminated.…”
Section: Introductionmentioning
confidence: 99%